Tayma, Saudi-Arabien. Bauwerkserhaltung. Die Arbeiten der Jahre 2015 bis 2017 - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2018)
In the framework of the conservation and restoration concept for the archaeological site of Tayma, work focused on the implementation of conservation measures on remains of a temple building which has been selected for future presentation within the tourist development of the site. Regular monitoring provided useful information for the planning of future restoration work. Backfilling operations, aimed at ensuring a long-term protection, continued in trenches with a completed archaeological documentation. A booklet and a documentary video on the protection of the architectural remains at Tayma were published. In 2017 a first public on-site event took place, constituting a model case for the post-excavation use of the site.